Implementasi Metode Vikor Dalam Menentukan Buku Berdasarkan Tren Referensi Konsumen Pada Toko Gramedia - Adjie Satria; Hasdiana; Edrian Hadinata (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
In the current digital era, changes in the book industry are very noticeable. Consumers are now more likely to look for references and buy books online. Easy access to the internet and the existence of e-commerce platforms have changed the way people search for and buy books. Apart from that, social media has also become an important channel for sharing book reviews and recommending reading to others. One of the shops affected by this digital era is the Gramedia bookstore, as one of the leading bookstores in Indonesia, experiencing several problems that need to be overcome in carrying out its operations. One of the main problems is competition with e-commerce platforms and online bookstores that offer books at lower prices, big discounts and fast delivery. This makes Gramedia have to look for strategies to remain competitive and attract customers to prefer shopping at physical stores or Gramedia online stores. Apart from that, Gramedia is also faced with changes in consumer patterns. More and more consumers are turning to reading books in digital or e-book form, which has an impact on physical book sales. Gramedia stores need to adapt their offerings to increasingly changing consumer preferences, as well as find ways to promote the benefits of reading and maintain interest in reading books amidst the abundance of digital entertainment and other activities. The VIKOR method is a useful tool in making complex decisions, such as determining books based on consumer reference trends in Gramedia Stores.